The new leaders : leadership diversity in America - Morrison, Ann M. (San Francisco : Jossey-Bass Publishers, 1996)
Business
Keywords: Leadership; Leadership diversity; Executives; Women executives; Minority executives; Affirmative action programs; Leadership strategy; Organizational change